Prevalence and risk factors of childbirth-related post-traumatic stress symptoms - Modarres Maryam; Afrasiabi Sedigheh; Rahnama Parvin; Montazeri Ali (BMC, 2012)
Abstract Background There is evidence that traumatic birth experiences are associated with psychological impairments. This study aimed to estimate the prevalence of childbirth-related post-traumatic stress symptoms and its obstetric and perinatal risk factors among a sample of Iranian women. Methods This was a cross-sectional study carried out in Bushehr, Iran during a 3-months period from July to September 2009. Data were collected from all women attending eleven healthcare centers for postnatal care 6 to 8 weeks after childbirth. Those who had a traumatic delivery were identified and entered into the study. In order to assess childbirth-related post-traumatic stress, the Post-traumatic Symptom Scale-Interview (PSS-I) was administered. Data on demographic, obstetric and perinatal characteristics also were collected. Multivariate logistic regression was performed to examine the association between childbirth-related post-traumatic stress and demographic and obstetric and perinatal variables. Results In all, 400 women were initially evaluated. Of these, 218 women (54.5%) had a traumatic delivery and overall, 80 women (20%) were found to be suffering from post-partum post-traumatic stress disorder (PTSD). Multiple logistic regression analysis revealed that post-partum PTSD was associated with educational level, gestational age at delivery, number of prenatal care visits, pregnancy complications, pregnancy intervals, labor duration, and mode of delivery. Conclusions The findings indicated that the prevalence of traumatic birth experiences and post-partum PTSD were relatively high among Iranian women. The findings also indicated that obstetric and perinatal variables were independently the most significant contributing factors to women's post-partum PTSD. It seems that a better perinatal care and supportive childbirth might help to reduce the burden of post-partum PTSD among this population.